أثر الثقة بين الشركاء على الابداع الاداري من خلال مشاركة المعرفة في المشاريع المشتركة. "دراسة حالة مؤسستي صناعة الكوابل (فرع جنرال كابل) ولافارج بسكرة" - شويخي, اسماعيل; غقال, إلياس (جامعة الوادي - University of Eloued, 2023)
هدفت هذه الدراسة إلى تحليل أثر الثقة بين الشركاء على الابداع الاداري من خلال مشاركة المعرفة في المشاريع المشتركة بين المؤسسات الجزائرية والاجنبية من وجهة نظر عمال المشروع المشترك. أجريت الدراسة بمؤسسة صناعة الكوابل ومؤسسة لافارج ببسكرة، وشملت عينة الدراسة 98 إداريا. أظهرت نتائج اختبار فرضيات الدراسة إلى: وجود أثر ذو دلالة إحصائية للثقة بين الشركاء على الابداع الإداري من خلال مشاركة المعرفة، كما أشارت النتائج الى قبول الفرضيات الفرعية؛ أي وجود أثر ذو دلالة إحصائية للثقة بين الشركاء على مشاركة المعرفة، وجود أثر ذو دلالة إحصائية لمشاركة المعرفة على الابداع الإداري، وجود أثر ذو دلالة إحصائية للثقة بين الشركاء على الابداع الإداري بمؤسستين محل الدراسة. The study aimed to analyze the impact of trust between the partners on administrative creativity through knowledge sharing in joint projects between Algerian and foreign institutions from the point view of workers. The study was conducted at the Cable Industry Corporation and Lafarge Corporation in Biskra, the study sample included 98 administrators. The results of testing the hypotheses of the study showed that: there is a statistically significant effect of trust between partners on administrative creativity through knowledge sharing, and the results indicated that the sub-hypotheses were accepted, there is a statistically significant effect of trust between partners on knowledge sharing, there is a statistically significant effect of knowledge sharing on administrative creativity, and there is a statistically significant effect of trust between partners on administrative creativity in the two institutions under study.
The impact of trust between partners on administrative creativity through sharing knowledge in joint projects. case study:cable industry establishments (General Cable Branch) and Lafarge Biskra
مقال
Keywords: الابداع الإداري، ; مشاركة المعرفة، ; الثقة بين الشركاء، ; اكتساب المعرفة ; لمشاريع المشتركة،; trust, knowledge sharing, administrative creativity, joint ventures, knowledge acquisition